Analisis Yuridis Pertimbangan Hakim dalam Putusan Perbuatan Melawan Hukum atas Penguasaan Sepihak Tanah (Studi Putusan Nomor 57/Pdt.G/2024/PN.Tjk) - Elsa Septi Berliana; Syamsuddin Pasamai (Universitas Medan Area, 2026)
This study aims to analyze judicial considerations in deciding unlawful acts related to unilateral land possession based on Decision Number 57/Pdt.G/2024/PN.Tjk. The research focuses on how judges assess the elements of unlawful acts and their conformity with legal certainty and justice principles. This research employs a normative juridical method with a statute approach, a conceptual approach, and a case approach. Data were collected through literature and document study, and analyzed qualitatively using legal interpretation. The results indicate that judicial considerations have fulfilled the elements of unlawful acts under Article 1365 of the Indonesian Civil Code, including act, fault, damage, and causality. The study also finds that judges not only emphasize legal certainty but also ensure substantive justice, particularly in protecting good-faith buyers.